2017
DOI: 10.1186/s12889-017-4467-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression, suicidality, and alcohol use disorder among people living with HIV/AIDS in Nigeria

Abstract: BackgroundPeople Living with HIV/AIDS (PLHIV) face various day-to-day and long-term personal, interpersonal, social, physical and psychological challenges as a result of, and in addition to the health conditions they are susceptible to due to their HIV status. There is a dearth of large-scale research to provide robust prevalence estimates of mental health problems among PLHIV, especially in Nigeria. This study aimed to ascertain the prevalence and factors associated with major depressive episodes, suicidality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
90
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 60 publications
7
90
2
1
Order By: Relevance
“…Psychological disorders such as depression are known to significantly increase the risk of suicidality. This is in keeping with previously documented research, which have demonstrated a significant relationship between depression and suicidality . It is consistent with the fact that depression reduces functioning and overall quality of life.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Psychological disorders such as depression are known to significantly increase the risk of suicidality. This is in keeping with previously documented research, which have demonstrated a significant relationship between depression and suicidality . It is consistent with the fact that depression reduces functioning and overall quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Socio‐demographic factors such as marital status and living status also showed significant relationship with suicidality. Consistent with findings from other studies, the proportion of people diagnosed with suicidality were significantly less in the group of participants who were “married or cohabiting.” This may be attributable to the fact that they may be getting adequate support from their spouses. Thus reinforcing the possible role of marriage as a protective factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations